Fuzzy logic inverter controller in photovoltaic applications: Issues and recommendations - Hannan M.A.; Ghani Z.A.; Hoque M.M.; Ker P.J.; Hussain A.; Mohamed A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer circuits; Control systems; Fossil fuels; Fuzzy logic; Membership functions; Photovoltaic cells; Power control; Power converters; Renewable energy resources; User interfaces; Alternative energy source; Conventional energy sources; Fuzzy logic controllers; inverter; Photovoltaic applications; Photovoltaic systems; Renewable energy source; Research and development; Controllers